Brief Review on Apoptosis in Microbial Infection - Alanazi, Abdulaziz; Alanazi, Mishal E.; Alanazi, Arwa F.; Alanazi, Amani F.; Alanazi, Badi; Alanazi, Fahad; Alanazi, Abdulmajeed; Alanazi, Abdulrahman Q.; Alenzi, Faris Q. (New Ideas Concerning Science and Technology Vol. 11, 2021)
Apoptosis represents an important process in the pathogenesis of a number of human diseases. Because apoptosis represents a fundamental process in the response to several infections it may represent a therapeutic target for their treatment. There is thus likely to be future clinical relevance in harnessing our growing knowledge both of apoptotic mechanisms, and their regulation, in the search to achieve modalities for therapeutic benefit. This brief review aims to summarize what we currently know about the role of apoptosis in response to a range of microbial infections (including bacterial and viral).